1967
DOI: 10.1063/1.1754880
|View full text |Cite
|
Sign up to set email alerts
|

SYNTHETIC PROUSTITE (Ag3AsS3): A NEW CRYSTAL FOR OPTICAL MIXING

Abstract: Frequencydependent negative photoconductivity and related dielectric behavior in singlecrystal proustite Ag3AsS3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1969
1969
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…However, we cannot find the bond susceptibility in the same way, because there is no equivalent structure in 3m which has only two atoms in the formula. So we try to decompose the susceptibility into the individual bonds by using the bond-additive principle: Hulme (1967), Boggett and Gibson (1968);Warner (1968).…”
Section: Other Ternary Compoundsmentioning
confidence: 99%
“…However, we cannot find the bond susceptibility in the same way, because there is no equivalent structure in 3m which has only two atoms in the formula. So we try to decompose the susceptibility into the individual bonds by using the bond-additive principle: Hulme (1967), Boggett and Gibson (1968);Warner (1968).…”
Section: Other Ternary Compoundsmentioning
confidence: 99%
“…Using the notation of Hulme et al [1 ], The measurements of r22 and (neZr33 --no3rl3) were made using the arrangement shown in fig. 2.…”
Section: Measurementsmentioning
confidence: 99%
“…Hulme et al [1 ], reported that the non-linear coefficients of proustite are thirty to fifty times those of KDP and since it is transparent from 0.6 to 13/zm its application as a CO2 laser modulator has been considered.…”
Section: Introductionmentioning
confidence: 99%
“…High-quality and rather large proustite single crystals were first grown by Hulme with co-workers [3] using the Stockbarger method.…”
Section: Introductionmentioning
confidence: 99%